Semi-supervised learning of facial attributes in video - Cherniavsky, N; Laptev, I; Sivic, J; Zisserman, A (Springer, 2013)
In this work we investigate a weakly-supervised approach to learning facial attributes of humans in video. Given a small set of images labeled with attributes and a much larger unlabeled set of video tracks, we train a classifier to recognize these attributes in video data. We make two contributions. First, we show that training on video data improves classification performance over training on images alone. Second, and more significantly, we show that tracks in video provide a natural mechanism for generalizing training data – in this case to new poses, lighting conditions and expressions. The advantage of our method is demonstrated on the classification of gender and age attributes in the movie “Love, Actually”. We show that the semi-supervised approach adds a significant performance boost, for example for gender increasing average precision from 0.75 on static images alone to 0.85.